Procurement and Politics - Migone, Andrea. author. aut Link
IX, 156 p. 4 illus., 2 illus. in color.
Keywords: This open access book compares the experiences of large-scale military procurement in Canada and Australia. Focusing on the recent frigate and jet-fighter programmes, it demonstrates how delays suffered in delivering weapons systems and platforms in these countries have been caused by misalignments between the strategic requirements set out by the armed forces and government defence policies. By bringing the insights of public management and administration to those of defence studies, the book presents policy options that will help improve the nature of future large-project military procurement. It will appeal to scholars and students of public administration, public management, and defence studies, as well as practitioners and policymakers. Andrea Migone is Assistant Professor at Toronto Metropolitan University, Canada. He has worked both in academia and the public service in the area of public policy, procurement and public administration. Alexander Howlett is a Researcher at the Canadian War Studies Association. His research interests include military and naval history. Michael Howlett is Burnaby Mountain Professor and Canada Research Chair in the Department of Political Science at Simon Fraser University, Canada. He specializes in public policy analysis, political economy, and resource and environmental policy.